Salt intake in kidney disease--a missed therapeutic opportunity? - Lambers Heerspink, Hiddo J.; Navis, Gerarda J.; Ritz, Eberhard (Nephrology, dialysis, transplantation, 2012)
Although signiﬁcant progress has been made in the treatment of chronic kidney disease (CKD), treatment is not yet satisfactory, particularly when it is started in the late stages of the disease. Novel modes of intervention to mitigate the burden of disease are required. The reduction of dietary salt intake (which is high in the industrialized world) is one such option. Better understanding of the deleterious effects of salt on renal and cardiovascular health is necessary to raise awareness of the importance of reduction of the salt content in food products. Therefore, we (i) review pathways through which high salt intake exerts damaging effects, (ii) provide an assessment of recent observational studies linking dietary salt intake to the progression of renal and cardiovascular disease and (iii) discuss the interaction between salt intake and rennin-angiotensin-aldosterone-system inhibitors, i.e. the ﬁrst choice antihypertensive agents for the treatment of CKD.